WISE USE OF TECHNOLOGY FOR DIGITAL COMMUNICATION MEDIA THAT SUPPORTS THE STRENGTHENING OF DIGITAL LITERACY - Putu Gde Sukarata; Made Sukma Manggala; I Gede Titah Pratyaksa (JKKB: Jurnal Kajian Komunikasi Budaya (JCCS: Journal of Cultural Communication Studies), 2024)
Technological advances, especially in the field of information today, cannot be dammed so rapidly changes at any time. This technological progress changes the lifestyle of people. Information technology is a technology used to process data, including processing, obtaining, compiling, storing, manipulating data in various ways to produce quality information, namely relevant, accurate and timely information, which is used for personal, business, and government and is strategic information for decision making. But this progress must be balanced with several stages so that it can be used well such as knowing the existence of technology, understanding of technology and using it. Besides that, in recent years since Covid-19 of its use has increasingly shown the number of increases. In early 2023 echoed about digital literacy by the government which contained 4 supporting pillars, namely digital culture, digital ethics, digital capable and digital safe. Digital culture is almost 100% fulfilled but for some other points have not produced good results. Research provides solutions that strengthen digital literacy mentioned above.